2010
DOI: 10.3109/00016340903508627
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum hysterectomy and cesarean delivery: a population‐based study

Abstract: In this population, primary and repeat cesarean deliveries are associated with an increased risk of peripartum hysterectomy. These results are of particular concern given the steady increase in the cesarean delivery rate in many countries. The pathological mechanism of this association requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
28
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 24 publications
7
28
0
1
Order By: Relevance
“…10 It is known from multiple studies, that caesarean section is associated with an increased risk of EPH. [11][12][13][14][15][16][17][18] This was confirmed by a recent systematic review from de la Cruz et al 1 The authors identified that Caesarean section, either as a previous history or as the current mode of delivery, was strongly and consistently associated with an increased risk of EPH. 1 Stanco et al reported that 43.4% of their emergency hysterectomies were done because of uterine atony, while 33.9% were due to placenta previa with accreta .19 A study from the same institution in 1993 stated that their primary indication was placenta accreta, the problem in 45% of cases, followed by uterine atony, with 20%.…”
Section: 2supporting
confidence: 59%
“…10 It is known from multiple studies, that caesarean section is associated with an increased risk of EPH. [11][12][13][14][15][16][17][18] This was confirmed by a recent systematic review from de la Cruz et al 1 The authors identified that Caesarean section, either as a previous history or as the current mode of delivery, was strongly and consistently associated with an increased risk of EPH. 1 Stanco et al reported that 43.4% of their emergency hysterectomies were done because of uterine atony, while 33.9% were due to placenta previa with accreta .19 A study from the same institution in 1993 stated that their primary indication was placenta accreta, the problem in 45% of cases, followed by uterine atony, with 20%.…”
Section: 2supporting
confidence: 59%
“…All three Canadian studies reported incidence rates less than 1.0 per 1000 deliveries [11][12][13]. The 22 studies conducted in Europe also had incidence rates under 1.0 per 1000 [2,4,5,9,[14][15][16][17][18][19][20][21][22][23][24][25] except for four studies in Italy, Austria and Greece [26][27][28][29]. Two studies conducted in Oceania reported incidence rates less than 1.0 per 1000 deliveries [30,31].…”
Section: Incidence Of Emergency Peripartum Hysterectomymentioning
confidence: 96%
“…O risco de morte materna é superior 7 , bem como a ocorrência de infecção, quadros hemorrágicos 8 , acidentes anestésicos 9 , histerectomia pós-parto 10 , ruptura uterina 7,11 , que tornam a morbidade materna relativamente mais acentuada do que no parto vaginal 12 . Complicações tardias, principalmente as relacionadas à placenta prévia e os graus variados de acretismo, estão diretamente relacionadas ao antecedente de cesárea 13,14 .…”
Section: Introductionunclassified